The relationship of cognitive performance to concurrent symptoms, cancer- and cancer-treatment-related variables in women with early-stage breast cancer: a 2-year longitudinal study - Lyon, Debra E. (J Cancer Res Clin Oncol, 2016)
PURPOSE: Cognitive dysfunction in women with breast cancer continues to be an area of intense research interest. The prevalence, severity, timing, and cognitive domains that are most affected, as well as the contribution of cancer and its treatments to cognition, remain unresolved. Thus, longitudinal studies are needed that examine cognitive function during different stages of breast cancer treatment and survivorship. This longitudinal trial followed women with early-stage breast cancer, prior to chemotherapy through 2 years survivorship. METHODS: In women with early-stage breast cancer (N = −75), performance-based assessment of nine cognitive domains was performed at five time points beginning prior to chemotherapy and finishing 24 months after initial chemotherapy. Linear mixed effects models were used to examine the temporal changes in cognitive performance domains, while adjusting for cofactors, including those related to individuals, tumor attributes, chemotherapy (adjuvant or neoadjuvant), radiation, endocrine therapy, and concurrent symptoms. RESULTS: At baseline, scores on reaction time, complex attention, cognitive flexibility, executive function, and visual memory were lower than 90. At 2 years, all domains improved except for the memory domains (verbal, visual, and composite). Scores on six domains (psychomotor speed, reaction time, complex attention, cognitive flexibility, and visual memory) remained lower than 100 at 2 years. Neoadjuvant chemotherapy and fatigue had strong inverse relationship with cognitive functioning at multiple time points. CONCLUSION: The low performance-based cognitive scores at baseline and over time warrant further study. Although most scores improved over time, memory did not improve. In all, the level of cognitive function is lower than expected for a majority college-educated sample. Thus, future studies are warranted to replicate these findings and to develop methods for identifying women with cognitive dysfunction pretreatment and into survivorship.